The effect of the size of pedicle screw on the long-term radiological and clinical results of short-segment posterior instrumentation in the management of thoracolumbar vertebral fractures - Anıl Murat Öztürk; Onur Süer; Selahaddin Aydemir; Bünyamin Kılıçlı; Ömer Akçalı (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: It was aimed at evaluating the effect of the size of the pedicle screw placed on the fractured vertebra on the long-term radiological and clinical results of short-segment posterior instrumentation applied in the surgical treatment of thoracolumbar vertebral fractures.